Phospholipid polymer hydrogels with rapid dissociation for reversible cell immobilization. Issue 14 (11th January 2022) - Moriwaki, Sachi; Yoshizaki, Yuta; Konno, Tomohiro
Abstract : Polymer hydrogels were prepared via gently mixing a PMB–MAPBA and PVA. The hydrogels can be easily dissociated after the addition of d -sorbitol, and immobilize cells without any reduction in bioactivity. Abstract : A reversible and cytocompatible cell immobilization polymer matrix with a rapid dissociation rate was prepared using a zwitterionic phospholipid polymer bearing phenylboronic acid and poly(vinyl alcohol) (PVA). A reversible and spontaneously forming phospholipid polymer hydrogel is reported for use as a cell immobilization matrix which caused no invasive damage to the cells. To improve the possibility of applying the hydrogels as a reversible cell immobilization matrix, the stimuli-responsive dissociation rate of polymer hydrogels was designed to have a more rapid rate to ease the recovery of the immobilized cells. In this study, a phospholipid polymer containing 3-methacrylamide phenylboronic acid (MAPBA) as the phenylboronic acid unit was synthesized. The water-soluble phospholipid polymer (PMB–MAPBA) can spontaneously form polymer hydrogels after mixing with PVA solution under normal pressure, room temperature, and neutral pH conditions. Also, the dissociation of the hydrogels after the addition of d -sorbitol completely occurred within 10 minutes. The cells were easily immobilized on the hydrogels during the preparation process. Also, the recovery ratio of the immobilized cells was improved due to the rapid dissociation of the hydrogels. The reversible and spontaneously formed phospholipid polymer hydrogels are promising for use as soft materials for platforms for cell engineering.